1987
DOI: 10.1126/science.3563496
|View full text |Cite
|
Sign up to set email alerts
|

It Is Diprotonated Inorganic Phosphate That Depresses Force in Skinned Skeletal Muscle Fibers

Abstract: The increases in the intracellular concentrations of inorganic phosphate and hydrogen ion accompanying fatigue of skeletal muscle appear to be the most important metabolic changes associated with the decrease in contractile force. Experiments on chemically skinned single fibers from rabbit psoas muscle with pH ranging between 6 and 7.25 demonstrate that the depression of maximal calcium-activated force by inorganic phosphate correlates nicely with the concentration of the acidic (diprotonated) species. Therefo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

25
115
4

Year Published

1993
1993
2016
2016

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 181 publications
(144 citation statements)
references
References 29 publications
25
115
4
Order By: Relevance
“…This observation might be explained, in part, by the increased concentration of dihydrogen phosphate (H2PO4 -) that occurs in acidic (pH 6.2) compared with neutral conditions (pH 7.0). 61 The dihydrogen phosphate species is more closely correlated to the decline in maximal force during in vivo fatigue compared with either the monohydrogen phosphate or the pH changes alone. 18,48,95 However, whether dihydrogen phosphate is the dominant fatigue-inducing phosphate species or merely serves as a better marker of the totality of metabolic by-products accumulating within the intracellular milieu remains unknown.…”
Section: +mentioning
confidence: 99%
See 1 more Smart Citation
“…This observation might be explained, in part, by the increased concentration of dihydrogen phosphate (H2PO4 -) that occurs in acidic (pH 6.2) compared with neutral conditions (pH 7.0). 61 The dihydrogen phosphate species is more closely correlated to the decline in maximal force during in vivo fatigue compared with either the monohydrogen phosphate or the pH changes alone. 18,48,95 However, whether dihydrogen phosphate is the dominant fatigue-inducing phosphate species or merely serves as a better marker of the totality of metabolic by-products accumulating within the intracellular milieu remains unknown.…”
Section: +mentioning
confidence: 99%
“…10,18,95 Subsequent experiments that exposed skinned single muscle fibers to fatiguing concentrations of Pi (~30 mM) and H + (pH 6.2 to 6.5) showed that these ions dramatically reduce maximal isometric force, 15,38,61 unloaded shortening velocity, 13 and peak power, 24,46,58 providing strong evidence that these ions play a causative role in the fatigue process. More specifically, because these experiments were , and thus with a fully activated thin filament, it suggests that these depressive effects are due, in part, to a direct effect on the actomyosin crossbridge.…”
mentioning
confidence: 99%
“…Several of these studies looked at recovery of isolated animal (Nassar-Gentina, et al, 1978;Nosek, et al, 1987;Spande & Schottelius, 1970) and human muscles (Bigland-Ritchie et al, 1978;Bogdanis et al, 1995;Boska et al, 1990;Harris et al, 1976;Hultman et al, 1967;McCann et al, 1995;Takahashi et al, 1995) in which the modes of contraction were not specific to the types of contraction typically used in strength training or testing. Many of the earlier findings on exercise recovery were based on various anaerobic exercises such as isometrics (Boska et al, 1990), electrical stimulation (Bigland-Ritchie et al, 1978), over-ground sprinting (Balsom, Seger, Sjodin, & Ekblom, 1992), or cycle sprinting (Bogdanis et al, 1995).…”
Section: Obtaining An Optimal Interset Rest Periodmentioning
confidence: 99%
“…Historically, basic research has primarily looked at exercise recovery in controlled laboratory settings using isometric and exhausting dynamic exercise (Bigland-Ritchie, Jones, Hosking, & Edwards, 1978;Bogdanis, Nevill, Boobis, Lakomy, & Nevill, 1995;Boska, Moussavi, Carson, Weiner, & Miller, 1990;Harris, Edwards, Hultman, Nordesjo, Nylind, & Sahlin, 1976;Hultman, Bergstrom & McLennan Anderson, 1967;McCann, Mole, & Caton, 1995;Nassar-Gentina, Passonneau, Vergara & Rapoport, 1978;Nosek, Fender, & Godt, 1987;Spande & Schottelius, 1970;Takahashi, Inaki, Fujimoto, Katsuta, Anno, Niitsu, et al, 1995).…”
Section: Obtaining An Optimal Interset Rest Periodmentioning
confidence: 99%
“…Within myocytes, metabolic products of ATP hydrolysis in the cytoplasm such as inorganic phosphate (Pi), protons (H + or pH), and ADP have often been considered as agents that could disrupt force generation at the sarcomere level (Fabiato and Fabiato, 1978;Cooke and Pate, 1985;Metzger and Moss, 1987;Nosek et al, 1987Nosek et al, , 1990Kushmerick, 1988, 1995;Cooke et al, 1988;Godt and Nosek, 1989;Pate and Cooke, 1989;Metzger and Moss, 1990a,b;Pate et al, 1995Pate et al, , 1998Wiseman et al, 1996;Karatzaferi et al, 2003Karatzaferi et al, , 2008. These effects may be due to direct binding to proteins, or due to a more global alteration of cellular energetics ( G ATP ) in the myocyte (Karatzaferi et al, 2004).…”
mentioning
confidence: 99%